Portrait photograph of an unidentified child, possibly male (location unknown) - Thayer, Alexander Wheelock, 1817-1897 (previous owner):::Collector:::::::::::: (2023)
Portrait photograph of an unidentified child, possibly male (undated) from the personal collection of Alexander Wheelock Thayer.